Obstetric Anal Sphincter Injuries: Compliance With ACOG Postpartum Care Recommendations [22L]. (May 2020) - Bates, Kari; Elkattah, Rayan; Kharoufeh, Anton
Abstract : INTRODUCTION: Severe obstetric lacerations that include the anal sphincter complex are associated with increased risk for short and long term complications. ACOG gives postpartum care recommendations to improve outcomes, including stool softeners and oral laxatives with counseling to avoid constipation, pain management with NSAIDs and opiate-containing analgesics, and one dose of perioperative antibiotics. The objective of this study was to assess compliance with these ACOG recommendations at a tertiary care hospital in Central Illinois. METHODS: An IRB-approved retrospective observational study was done on patients that had vaginal deliveries complicated by OASIS in the calendar year of 2018. Compliance percentages were obtained for each recommendation. Anything less than 100% compliance was considered inadequate. RESULTS: A total 45 patients were found to have vaginal deliveries complicated by OASIS in 2018. One wound complication was identified to date. Compliance was less than 100% in all parameters. Only 20% received perioperative antibiotics. While inpatient, compliance rates varied from 49% to 87% of patients receiving adequate postpartum care. Upon discharge from the hospital in the postpartum period, compliance rates varied from 4% to 47% of patients receiving adequate prescriptions or counseling for medication use. CONCLUSION: Our results indicate that compliance with ACOG guidelines is inadequate at a busy tertiary care center in Central Illinois. Of particular concern is the lack of patients receiving adequate counseling and prescriptions for medications (stool softeners, NSAIDs, opiates) upon discharge from the hospital. Interventions are currently being investigated and the results of implementation will be a source of future studies.